Kidney biopsy as a predictor for renal outcome in ANCA-associated necrotizing glomerulonephritis - Bajema, Ingeborg; Hagen, E. C.; Hermans, J.; Noël, L. H.; Waldherr, Rüdiger; Ferrario, F.; Woude, Fokko J. van der; Bruijn, J. A. (Kidney international, 1999)
BACKGROUND: In kidney biopsies of patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated systemic vasculitis, a variety of histopathological lesions occur, and their relationship to renal outcome is virtually unknown. This multicenter European study reports a clinicopathological analysis of biopsies from 157 patients with systemic vasculitis. METHODS: The biopsies were evaluated according to a previously standardized scoring protocol. Serum creatinine values were measured at the time of biopsy and one year later. In addition, the lowest creatinine level during follow-up was taken into account as the optimum level of renal function recovery. The clinical prognostic value of the histopathological parameters was analyzed with the Kruskal-Wallis one-way analysis of variance and the Mann-Whitney U-test. RESULTS: The percentage of normal glomeruli correlated most significantly with renal outcome at all points of measurement (all P < 0.001). Other lesions predicting for renal function were glomerular sclerosis (P < 0.0005 at one year after the biopsy), diffuse interstitial infiltrates (P < 0.0001 at entry, P < 0.0003 at one year), tubular necrosis (P < 0.0025 at entry), and tubular atrophy (P < 0.002 at entry, P < 0.0002 at one year). CONCLUSION: Traditionally, attention is focused on the extent of active lesions in the renal biopsy in order to determine the severity of renal disease and its implication for renal outcome. Because of their significant impact on renal function, combined with their easy recognition, we recommend the use of the percentage of normal glomeruli in an adequate biopsy in predicting renal function of patients with systemic vasculitis.
Available online: 1 November 1999
Gesehen am 30.06.2022